การจัดเวลาเรียนและโอกาสในการเรียนรู้ของนักเรียน โรงเรียนประถมศึกษาที่มีบริบทแตกต่างกัน ในจังหวัดเชียงใหม่ - ฐิติมา ญาณะวงษา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The purposes of this study were to study 1) time management and instructional activities that have different contexts in Chiang Mai primary schools, 2) learning opportunities of students that have different of contexts and time management in Chiang Mai primary schools. The sample were selected by multi-stage sampling that consisted of 6 head of academic affairs, 6 home room teachers, 48 teachers from eight subject areas, and 30 students of Prathom Suksa 6th in 6 schools under Chiang Mai Primary Educational Service Area Office 1. The instruments of this study were 1) an analysis form of time management characteristics in overall with school planning 2) an analysis form of time management characteristics and learning opportunities in each subject areas 3) a teacher’s questionnaire about using teaching plans and promoted students’ learning opportunities in classroom and 4) an interview form about learning opportunities of students. The data were analyzed by classifying data into groups, frequency, percentage and interpretation average, presented in the form of descriptive analysis. The result of the study were as followed; Time management and learning opportunities of Pratom Suksa students in both contexts were similar as time management; the periods of time in schedule were set according to The Basic Education Core Curriculum B.E. 2551 (A.D. 2008). The first period was start from 08.30 to 09.30 and the last session was from 14.30 to 15.30 . Foreign language substance was set in the morning session while the extra curriculum activities were set in the afternoon session. Teaching and learning, activities focused on practical skills needed more time provision. Activities with variety media and fun activities needed control of a teacher. More time on independent assignment was needed Learning opportunities ; for physical development; most opportunities provided by learning through movement and gross motor development in physical education, dancing arts and agriculture, and fine motor development was mostly enhanced through painting and writing activities. For cognitive development, thinking skills , process and self-knowledge conclusion were the most activities provided. For social development, most opportunities were enhanced through interaction with classmates at the highest level. In order that the issues were different as 1) Time management, the different found was the length during lunch time break, the one of the elementary schools was shorter than educational opportunity expansion schools2) Teaching and learning, elementary school teachers had the opportunity to have more flexible time to teach than the ones in educational opportunity expansion schools and 3) Learning opportunities, the difference found in enhancing emotional development, the elementary school mostly focused on distinguishing between the good or evil, right-wrong, suitable or unsuitable. While the educational opportunity expansion schools mostly focused on communication skills, and express emotion through activities.